RECEITA DOS CORTES SECUNDÁRIOS DA CARCAÇA DE MACHOS NELORE NÃO CASTRADOS ABATIDOS COM DIFERENTES PESOS E DENTIÇÕES - Fabiano Nunes Vaz; João Restle; João Teodoro Pádua; Paulo Santana Pacheco; Cristiane Amorim Fonseca; Mozer Manetti de Ávila (Ciência Animal Brasileira, 2013)
The objective of this work was to assess the income of deboning secondary cuts from non-castrated Nellore carcasses, slaughtered with different weights and dentition. Fourty animals with average initial weight at feedlot of 350 kg were used. The animals were divided into four groups: animals with 0 and two teeth, with carcass weight up to 238,0 kg (young and light carcass); 2-teeth animals with carcass weight ranging from 238,1 to 258,0 kg (young and medium carcass); 2-teeth animals with carcass weight above 258 kg (young and heavy carcass) and animals with four or six teeth, regardless of carcass weight (adults). The animals were confined and fed a diet calculated to achieve a weight gain of 1.2 kg/day. The study showed that carcasses of young animals show similarity in yields of most deboned cuts among weight classes and the four or six-teeth (adults) males were similar to young and medium animals and lower to young with heavy carcasses in some boneless cuts. We concluded that deboning primary cuts into secondary cuts represent considerable aggregation value to industry, emphasizing the efficiency of flank deboning process.